Dislocation mediated plastic flow in aluminum: Comparison between theory and experiment. (October 2017) - Le, K.C.; Tran, T.M.
Abstract: The theory of dislocation mediated plastic flow proposed by Langer, Bouchbinder, and Lookman is applied to compute the stress-strain curve of aluminum over a wide range of temperatures and strain rates. The parameter identification by the least squares method is provided leading to the excellent agreement with experiment.